Effect of Cu addition on sedimentary bacterial community structure and heavy metal resistance gene abundance in mangrove wetlands - Liao, Junxian; Xu, Ying; Zhang, Zuye; Zeng, Linfang; Qiao, Yue; Guo, Zhipeng; Chen, Jun; Jia, Bin; Shang, Chenjing; Chen, Si (Frontiers in Marine Science, 2023)
Introduction Mangroves are a unique ecosystem, but are often affected by heavy metal pollution. Bacterial communities in mangrove sediments usually respond to heavy-metal pollution stress by expressing specific heavy-metal resistance genes (HMRGs). Methods Multivariate statistics were performed on Metagenomics as well as environmental data to evaluated the effects of Cu addition on the sedimentary bacterial community structure. Results and discussion Using metagenomics technology, we found that the Shannon andChao1 indices of natural sediments were significantly higher than in sediments with artificially added Cu. Addition of Cu significantly altered bacterial community structure and diversity at the phylum, class and order levels in sediments. The relative abundance of HMRGs in Cuadded sediments was lower than that in natural sediments. Environmental factors that affect bacterial communities also affect HMRGs. However, the contribution of heavy-metal pollution to the change in HMRG abundance was much lower than its contribution to the change in the bacterial community, indicating that the relationship between HMRG abundance and heavy-metal pollution is complex and needs to be comprehensively studied.